MAKAM LEGENDA ORANG KAYO HITAM: SEBUAH ANALISIS HISTORIS - Mhd Ikhwan; Foni Refika Anggela (Nazharat: Jurnal Kebudayaan, 2019)
This article aims to describe the historical facts found in the legendary tomb of the Orang kayo hitam. The inscription begins with a brief history of Legend of the Orang kayo hitam then followed by the exposure of research results in the Tomb of legend Orang kayo hitam located in the village of Simpang Berbak District Tanjung Jabung Timur. The methods of study used are qualitative methods with data collection techniques in the form of observations, interviews, and documentation. Researchers conducted interviews in-depth with the tombs of the tomb of the Orang kayo hitam and the pilgrims who were dating to make a pilgrimage to the tomb. The results of this study include the history of the Orang kayo hitam, the hereditary lineage of the Orang kayo hitam, the love story of the Orang kayo hitam with the Princess Mayang mangurai, Keris Siginjai and the Orang kayo hitam, the Invisible Kingdom of the Orang kayo hitam, know the tomb of the Orang kayo hitam, Myths and traditions in the tomb of the Orang kayo hitam, the invention of the tomb of the Orang kayo hitam.